Pancasila Based Character Education to Form Good and Smart Citizens - Wiwik Eka Kusmawati; Ahmad Dion Ghojaji; Moh. Gufron Eramansyah; Riyanti Eka Putri; Siti Istianah; Masduki Asbari; AGUS PURWANTO (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
This study aims to describe the cultivation of Pancasila-based character education values ​​to form good and intelligent citizens. In other words, character education teaches youth to think intelligently so that they can overcome various kinds of new problems that exist, and increase their ability to blend in with other nations while maintaining their national identity and culture. This study uses data collection tools from articles on Google Scholar and google.com. The method of delivering material in this activity is through Zoom Meetings with the delivery of lectures and discussions. This research shows that Pancasila-based character education to form good and intelligent citizens is very important to implement because it contains religious character values, social care, independence, national spirit, democracy, tolerance, and discipline. Pancasila-based character education to form good and intelligent citizens is carried out in schools through the teaching and learning process and also in the family.